De Homero e Ruth Rocha: um estudo do processo de adaptação das personagens da Odisseia para jovens leitores. - Alves, Evandro Fantoni Rodrigues (2018)
The present study aims to study the process of literary adaptation of the epic poem attributed to Homer, Odyssey, in the adaptation of Ruth Rocha, from the perspective of the construction of the characters - Odysseus, Circe, and Athena. It was hypothesized that the process of construction and individualization of the characters is one of the elements that confers aesthetic quality to the work, and that if such characteristics were preserved in the adaptations, it is possible to maintain the aesthetic quality of the epic poem, regardless of the language for which it has been adapted. For the verification of this hypothesis, the qualitative, bibliographic and hypothetical-deductive method of research was used, through the reading of the corpus that composes this work, as well as the selected theoretical works that deal with the subjects necessary for the analysis, namely: concepts of adaptation, construction of characters, and discussions about the maintenance of aesthetic quality in antiquity and contemporaneity. The theoretical reference used for the analyzes was based on the concepts of literary adaptation of Jauss, presented by Diógenes Buenos Aires; in the reflections of Beth Brait, Fernando Segolin, Massaud Moisés and Anatol Rosenfeld, about the character; and the aesthetic values of antiquity as they are brought into classical poetics by Aristoteles and revisited by Segismundo Spina